THE INFLUENCE OF SOCIAL ENVIRONMENT ON THE USE OF CODE SWITCHING IN PANIMBANG DISTRICT - Dalpah Triwidiah, Vina Yuliani, Eneng Liah Khoiriyah (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
This study aims to examine the influence of social environment on the use of code switching in Panimbang Sub-district. Code switching refers to the switching of languages or dialects used in communicating between individuals in the community life in Panimbang Sub-district. This phenomenon is widespread in the Panimbang community, where more than one language is used in daily life, such as Sundanese, Javanese and Indonesian. Social, cultural, and educational factors are the main causes of the code switching phenomenon, and are influenced by factors such as social status, closeness between individuals, and local cultural habits. The results of this study show that the use of code switching has a positive impact on social relations between individuals, but there are also negative impacts, such as causing confusion for those who are less familiar. Therefore, it is important for people to preserve local languages, especially Sundanese and Javanese, in order to maintain cultural identity.